2016
DOI: 10.1017/s1049023x16001229
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hospitals’ Disaster Preparedness Plans in the Holy City of Makkah (Mecca): A Cross-Sectional Observation Study

Abstract: Makkah has experienced multiple disaster incidents over the last decade. The present research suggests that Makkah hospitals are insufficiently prepared for potential future disasters. This may represent a considerable threat to the health of both residents and visitors to Makkah. This study demonstrated that there is significant room for improvement in most aspects of hospital Emergency Operations Plans, in particular: reviewing the plan and increasing the frequency of multi-agency and multi-hospital drills. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 18 publications
10
43
0
Order By: Relevance
“…This gure is higher than what was reported in a Belgian study (53%). (10) Combined drills were conducted in collaboration with local agencies in very few hospitals, and this nding concurs with those of Wetter et al and Al-Shareef et al (15,21) In the present study, only half of the hospitals had a designated CBRN coordinator. A CBRN coordinator oversees CBRN preparedness activities.…”
Section: )supporting
confidence: 92%
See 3 more Smart Citations
“…This gure is higher than what was reported in a Belgian study (53%). (10) Combined drills were conducted in collaboration with local agencies in very few hospitals, and this nding concurs with those of Wetter et al and Al-Shareef et al (15,21) In the present study, only half of the hospitals had a designated CBRN coordinator. A CBRN coordinator oversees CBRN preparedness activities.…”
Section: )supporting
confidence: 92%
“…Without clearly de ned objective criteria and key performance indicators of minimum requirements for staff preparedness, it is not possible to assess hospital preparedness. (22) Many measures of disaster preparedness exist (15,24), one of which assess 3 associated competencies: general competencies, speci c competencies of emergency nurses, and rapid response competencies of rst-line healthcare providers (23). However, the CBRNE Plan Checklist was adapted and used in the present study because we found it to be most appropriate to the Saudi context.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…12 A growing number of studies in the literature reported facts about Kingdom of Saudi Arabia's disaster management and preparedness. [13][14][15][16][17][18][19][20] Bajow et al, 20 evaluated hospital disaster preparedness in Jeddah region, Kingdom of Saudi Arabia, and showed that although study hospital had the tools and quality indicators for emergency preparedness, staff are lacking the proper training and management of disaster. Moreover, quite a few studies have reported variety in staff knowledge, training and education regarding preparedness for disaster emergency incidents.…”
mentioning
confidence: 99%